O sonho feminino de Ícaro : a educação das pioneiras da aviação militar brasileira na Academia da Força Aérea - Baquim, Cristiane Aparecida (2008)
The present project has as objective present the educational process of militaries aviators graduation in the Air Force Academy (AFA), articulating to this questions that appeared from first feminine participation in a officer graduation course, to stablish the main rank of Brazilian Air Force (FAB). It treats of a qualitative search with ethnographic approach, developed in a military institution of FAB career officer graduation, considering all cadets since the first class that starts the Aviators Officers Graduation course in AFA in 2003, until the follow classes culminating in 2007, forming this as search participant. Search, finally, identify as the cadets themselves assimilated the educational process which submitted, searching outline an analysis about these school and social origin, of life in barracks, of learn-teach process, of flight learn of expectation as the career and the personal life, just as the type questions that emerged in consequence of their participation in the barracks atmosphere, traditionally masculine. Also were questioned some flight instructors that influenced in these cadets graduation, with intention demonstrate how these developed their work ahead this new reality, how organized the air instruction, how assimilated the cadets participation in the Air Instruction Squad atmosphere and what the perception they had in aviator learning, as cognitive as psychomotor and military. In organizationals terms, the study showed that didn t have, initially, a project structured aiming attend the questions resulting of women insertion in this atmosphere organized burocrateament and standardized according to discipline and hierarchy pillars. The changes that were happening, a posteriori, suggest that, inspite of atmosphere alterations reported, did not have a structural change capable to stablish new parameters to education and military organization. Finally, with the observations here presented wait with the developed studies in education area, harrowing the bonds between the civil academy and military academy, as show some-analysis that could contribute to a better adaptation of Brazilian Air Force organizational structure to military profile that wait graduate in AFA.